Spectrophotometric Methods for Determination of Plant Polyphenols Content and their Antioxidant Activity Assessment: an Overview - Harnafi, Hicham; Amrani, Souliman (Pharmacognosy Reviews)
Medicinal plants, as source of remedies, are widely used as alternative therapeutic tool for the prevention or treatment of many diseases. On the other hand, despite the remarkable progress in synthetic organic chemistry, over 25% of prescribed medicines in industrialized countries derived directly or indirectly from medicinal plants. Polyphenols, are the major plant secondary metabolites and represent the most studied phytochemicals. This family includes three major classes different by their specific chemical structure, we note: tannins, flavonoids, and anthocyanins. Many epidemiological and experimental studies have shown that flavonoid intake is inversely correlated with cancer, cardiovascular and cerebrovascular disease events. In this field, a number of polyphenols from medicinal plants have been shown to protect body against effects of oxidative stress. These phytochemicals react as free radical scavenging, reducing, and metal chelating substances. In this paper we present the major colorimetric techniques used to determine polyphenol content in medicinal plant extracts and the spectrophotometric assays employed to measure their antioxidant power.
Keywords: Polyphenols; Dosage; Antioxidant Effect; Methods